AN INVESTIGATION INTO THE DISCIPLINARY PRACTICES THAT INFLUENCE THE STUDENT UNREST IN PUBLIC SECONDARY SCHOOLS IN MERU COUNTY, KENYA - Marete, Jacob Bundi; Mugwe, Dr. Mary; Reche, Prof. George N. (IJRDO- Journal of Educational Research, 2017)
Since Kenya attained independence in 1963, students’ unrest in public secondary schools hasbeen on the rise, and thus students’ academic achievements and subsequently the economicprogress of Kenya has suffered the negative consequences of strikes. The purpose of the studywas to investigate the disciplinary factors that influence the student unrest in public secondaryschools in Meru County, Kenya. The research found that most schools do not follow progressivediscipline practices, and most schools did not have discipline committees where students whofelt unfairly treated can appeal the decision. Most of the disciplinary was done by studentleadership councils, and all public secondary school had rules and regulations that are known bystaff members and students.